A novel composite membrane pectin from Cyclea Barbata Miers blend with chitosan for accelerated wound healing. (July 2021) - Sari, Mayang; Tamrin,; Kaban, Jamaran; Alfian, Zul
Abstract: In this work, pectin derived from Cyclea Barbata Miers (CBM) was successfully blended with chitosan as a novel membrane and the physico-chemical analysis was investigated. Based on SEM analysis revealed that the chitosan/pectin blended membrane showed a rough surface texture compared to pristine chitosan with smooth and uniform membran. In addition, fourier-transform infrared spectroscopy (FTIR) analysis indicates that chitosan and pectin were successfully crosslinked, meanwhile x-ray diffraction (XRD) analysis found that pectin extracted from CBM exhibited crystalline structure. Thermal analysis based on thermogravimetric analysis (TGA) suggesting that chitosan/pectin blend membrane exhibited significant improvement in the thermal stability with residual mass of 54% at 360 °C. Furthermore, swelling degree, water vapor transmission rate (WVTR) and porosity of the chitosan/pectin blend membrane were 266%, 9.68 g/m 2 h, and 64%, respectively. Most importantly, in-vivo results indicated that the prepared membrane of chitosan/pectin immobilized with Musa Paradisiaca Linn (MPL) group had better wound closure with better wound reduction percentage than the gauze-treated wound (the control group). This finding revealed that the chitosan/pectin blend membrane could paves the way for future biomedical wound dressing application. Highlights: Pectin was extracted from Cyclea Barbata Miers at room temperature and collected via freeze-drying. Membrane was obtained from pectin and chitosan mixtures. The use of chitosan/pectin improves the swelling, water vapor transmission rate and porosity. Chitosan/pectin membrane was immobilized with ethanolic extract of Musa Paradisiaca Linn (MPL). The results showed a remarkable positive effect on accelerated wound healing.